La compagnie maritime Allan: de l'Écosse au Canada au XIXe siècle - Blondel-Loisel, Annie (L'Harmattan, 2009)
Keywords: Allan Royal Mail Line; Allan; Andrew; Allan; Hugh; Navigation

WHA looks at some Prominent Westmounters (The Westmount Historian, 2008)
Number: 2
Keywords: Lait; Magasins; Port; Quartiers; Quincaillerie; Westmount

Montreal Railway Terminals - Leduc, Michael (Michael Leduc, 2008)
Keywords: Canadien National; Canadien Pacifique; Chemins de fer; Gares

Pointe St. Charles Shop - Leduc, Michael (Michael Leduc, 2007)
Keywords: Chemins de fer; Grand Tronc

L'organisation spatiale du corridor du canal de Lachine au XIXe siècle - Desjardins, Pauline (Association des archéologues du Québec, 2006)
Keywords: Lachine (canal)

Voies pointelières d'hier et d'aujourd'hui - Desjardins, Pierre (Atelier d'histoire de Pointe-aux-Trembles, 2006)
Keywords: Chemins de fer; Navigation; Pointe-aux-Trembles; Quartiers

94 ans après la Conquête un premier navire français à Montréal - Gaudet, Sylvain (Montréal en tête, 2006)
issued: 2006-24-00
Keywords: Commerce de détail; Marchands; Port

KENNEDY, sir JOHN - Millard, J. Rodney (Dictionnaire biographique du Canada, 2005)

STEPHEN, GEORGE, 1er baron Mount Stephen - Reford, Alexander (Dictionnaire biographique du Canada, 2005)

SHAUGHNESSY, THOMAS GEORGE, 1er baron SHAUGHNESSY - Regehr, Theodore D. (Dictionnaire biographique du Canada, 2005)

ROSS, WILLIAM GILLIES - Ross, W. Gillies (Dictionnaire biographique du Canada, 2005)

Muddy Shore to Modern Port: Redimensioning the Montréal Waterfront Time-Space - Gilliland, Jason A. (The Canadian Geographer / Le Géographe canadien, 2004)
Number: 4
Keywords: Paysages; Port

Navigation and Waterpower : Adaptation and Technology on Canadian Canals - Desjardins, Pauline (The Journal of the Society for Industrial Archeology, 2003)
Number: 1
Keywords: Navigation; Énergie hydraulique

Behind the Scene of the Lachine Canal Landscape - Desloges, Yvon (The Journal of the Society for Industrial Archeology, 2003)
Number: 1
Keywords: Lachine (canal)

A Precipitous Decline, Steam as a Motive Power in Montreal : A Case Study of the Lachine Canal Industries - Gelly, Alain (The Journal of the Society for Industrial Archeology, 2003)
Number: 1
Keywords: Lachine (canal); Énergie hydraulique

Steam or Water Power? Thomas C. Keefer and the Engineers Discuss the Montreal Waterworks in 1852 - Ross, Susan M. (The Journal of the Society for Industrial Archeology, 2003)
Number: 1
Keywords: Aqueduc; Énergie hydraulique

CATELLI, CARLO ONORATO (Charles-Honoré) - Scardellato, Gabriele (Dictionnaire biographique du Canada, 2003)

Le canal de Lachine: l’eau à l’œuvre - Desloges, Yvon (Continuité, 2002)
issued: 2002-22-00
Keywords: Lachine (canal)

La rivière des Prairies - Dupont, Antonin (Il était une fois... Montréal-Nord, 2002)
issued: 2002-22-00
Keywords: Navigation; Rivière des Prairies

Programme d'inventaire archéologique de la Pointe-des-Seigneurs - Société d'archéomatique Chronogramme-Lauverbec (Société d'archéomatique Chronogramme-Lauverbec, 2002)
Keywords: Artisans; Confection; Fer et acier; Lachine (canal); Meunerie; Mouleurs; Ogilvie Flour Mills; Énergie hydraulique

Le Saint-Laurent, comme une rue principale - Franck, Alain (Continuité, 2001)
issued: 2001-22-00
Keywords: Navigation; Voie maritime

Redimensioning Montreal: Circulation and Urban Form, 1846-1918 - Gilliland, Jason A. (Université McGill, 2001)
Keywords: Incendies; Port; Rues

Le chemin de fer sur la glace - Lefort, Pierre (Histoire Québec, 2000)
Number: 1
Keywords: Canadien Pacifique; Chemins de fer; Longueuil; Ponts; Victoria (pont)

Steamboat connections : Montreal to Upper Canada, 1816-1843 - Mackey, Frank (McGill-Queen's University Press, 2000)
"In Steamboat Connections Frank Mackey gives us a narrative account of the first twenty-five years of steam navigation along the St. Lawrence and Ottawa Rivers. Relying on a wealth of primary archival sources, Mackey focuses on the development of steamer traffic from 1816 - when the foundations were laid for the first stage and steamboat line between Montreal and Upper Canada - to the early 1840s - when locks, canals, innovations, and human daring conquered the rapids on those rivers and allowed for navigation between Montreal and the Great Lakes. He shows how, starting in 1841, small steamers ran "the circuit" - down the rapids of the St. Lawrence to Montreal and then back up to Kingston and other Great Lakes ports via the Ottawa River and the Rideau Canal." "Mackey introduces the entrepreneurs who forged this important link between Montreal and the nation's interior and chronicles the course of their industry, correcting previous misinterpretations. He sheds light not only on steamboats but also on the social, commercial, and geographical development they made possible. He shows that the history of this country, a land with vast expanses and a harsh climate, cannot be fully appreciated without looking at the different modes of transportation that made it possible."–BOOK JACKET.
Keywords: Navigation